We Are All Monsters Now!: A Marxist Critique of Liberal Organization and the Need for a Revolutionary Monstrous Humanism. Issue 7 (29th August 2014) - Bloom, Peter
Abstract : Purpose: This paper investigates how Marxist accounts of capitalism and capitalists as 'vampiric' and 'cannibalistic' can challenge the exploitation underlying 'monstrosity' of the diverse 'liberal organization'. Design/methodology/approach: To bear out this argument, it will critically turn to Marx's original description of capitalism as 'vampire' like. It will do so by examining a range of theoretical and existing empirical research related themes of contemporary diversity. Findings: The paper argues that in order to avoid becoming capitalist monsters it is imperative to adopt an explicitly anti-capitalist Marxist perspective centring on themes of a 'monstrous' capitalism. Capitalist organizations, not only 'suck the blood of workers' but turns them into exploiting vampires, feeding on others for own profit and promotion. Yet it also expands on such readings by emphasizing the liberating possibilities that a more contemporary view of 'monsters' stressing radical diversity and difference can make to this Marxist critique. Originality/value: To this end, it illuminates how a perspective uniting these ideals, termed here as a 'revolutionary monstrous humanism', can effectively challenge the dehumanization of managerial control and market ideologies while also fighting for the right of individuals to express their heterogeneous and always evolving unique cultural identities.